The Role of Attitude in the Influence of Social Pressure, Product Features, and Brand Image on Android Brand Switching Decisions Among Gen-Z College Students - Khusnul Hairunnisa; M. Irfani Hendri; Ahmadi; Wenny Pebrianti; Bintoro Bagus Purmono (Al-Qalam Institue, 2026)
This study aims to examine the effects of social pressure, product features, and brand image on brand switching from Android to iPhone among Generation Z consumers, with attitude serving as a mediating variable. A quantitative research approach was employed using a survey method. Data were collected from 362 Generation Z university students who had previously used Android smartphones. The respondents were selected through purposive sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that social pressure, product features, and brand image have positive and significant effects on attitude. Furthermore, attitude has a positive and significant effect on brand switching from Android to iPhone. The mediation analysis reveals that attitude significantly mediates the relationships between social pressure, product features, and brand image with brand switching. These findings contribute to the consumer behavior literature by providing a deeper understanding of the factors influencing brand-switching decisions in the smartphone industry. The study also offers practical insights for smartphone marketers in developing strategies that strengthen consumer attitudes and enhance brand attractiveness to encourage switching behavior among Generation Z consumers.